Analysis of Solvency and Profitability Ratios of Financial Statements to Assess the Financial Performance of PT Bank Rakyat Indonesia, Tbk. - Musadat, Irfan Achmad; Putri, Dewi Yolanda (CV ODIS, 2025)
Assessment of a company's financial condition can be carried out by analyzing its financial statements. To determine whether the financial condition of the company is in good shape, various analyses can be conducted, one of which is ratio analysis. The purpose of this study is to evaluate the financial performance of PT. Bank Rakyat Indonesia Tbk based on financial ratio analysis. The analytical method used is descriptive analysis using solvency and profitability ratios. The data and information for this study were obtained from the Indonesia Stock Exchange. Based on the solvency ratio, PT. Bank Rakyat Indonesia Tbk is in a good position, meaning the company is able to pay its debts on time (solvable). From the profitability ratio perspective, there is a decline in profits from 2022 to 2023, indicating that the company has failed to generate increasing profits year over year.